A randomized control trial of platelet-rich plasma in supporting the recovery of postpartum levator ani muscle trauma (Faculty of Medicine Universitas Indonesia, 2022)
BACKGROUND Pelvic floor dysfunction (PFD) is mostly caused by childbirth levator ani muscle (LAM) trauma. We hypothesized that platelet-rich plasma (PRP) therapy could support the recovery of LAM in postpartum trauma. METHODS A prospective, single-blind, randomized control study was enrolled in primigravid women from November 2016 to July 2019 at 21 health facilities in Jakarta, Indonesia. Subjects were injected with autologous PRP or placebo at LAM during perineorrhaphy after childbirth. The primary outcome was regaining LAM strength and reducing levator hiatal area at 3 months postpartum. The LAM strength was examined by perineometer (cmH₂O), and levator hiatal area was examined by transperineal ultrasound (cm²) at antenatal and 3 months after delivery. Mann–Whitney U test and Wilcoxon signed-rank test were used for analysis. The study was registered in clinicaltrials.gov: NCT03021954. RESULTS Among 240 women, 58 were eligible for analysis. There were no differences in LAM strength and levator ani hiatal area at 3 months postpartum between the two groups (p = 0.583 and p = 0.185, respectively). CONCLUSIONS PRP therapy did not show a difference in the muscle recovery healing process.